Field Experimental Study on Mechanical Properties of Frame Support Structure Composed of Subway Foundation Pit Retaining Pile and Steel Strut Rigid Joint - Mingli Huang; Zhang Zhien; Bingyi Chen; Hongkun Wang (Advances in Civil Engineering)
In order to study the advantages of frame support structure composed of rigid joint between steel strut and retaining pile in restraining the lateral displacement of retaining structure and maintaining the stability of foundation pit, foundation pit failure test was carried out. Compared with the traditional support structure, which can only bear pressure composed of steel strut and retaining pile lap joint, the variation characteristics of pile lateral displacement and support axial force of frame support structure under the influencing factors, such as weak stratum, pit side loading, groundwater level rise, and support drop, are studied. The test results show that, compared with the traditional steel strut, the pile-strut frame support structure can not only bear the compressive stress, but also the tensile stress caused by the lateral displacement of the top of the retaining pile outside the foundation pit. The overall stability is better, and the axial force distribution of each layer of support is more uniform so as to reduce the overall lateral displacement of the retaining pile. In the process of foundation pit collapse, the frame support structure will not have the problem of strut falling, which can maintain part of the support capacity, prolong the collapse time of retaining piles, strive for more escape time for front-line construction workers, and reduce the number of casualties.